Paul Auster’s 4 3 2 1. Past Paradigms - I. B. Siegumfeldt (Revue LISA)
There is something strange about a cast of characters that comes in tetrads centering on duplicate yet different protagonists with identical names, and critics who argue that Auster’s mastodon novel, 4 3 2 1, marks a return to realism fail to take into account the inflated tone of the fabular woven into the texture of the narrative. Auster has worked with alternativity before, but 4 3 2 1 takes his penchant for unknowability to a new level. It installs a constitutive element of heterogeneity at the core of the text and sabotages readerly expectations. It would be far-fetched to argue that 4 3 2 1 forges a literary strategy, in which ‘myth’ and ‘the everyday’ converge, that is consonant with a new type of twenty-first century fiction which critics are currently at pains to define.